When Children Take the Lead - United Nations Office of the Special Representative of the Secretary-General on Violence Against Children (United Nations, 2021)
Milestones of the same decade, the United Nations Convention on the Rights of the Child (UNCRC) and the Internet together changed childhood forever, giving a new generation of children specific rights and an unprecedented opportunity to exercise them. At the same time, governments and organizations the world over have embraced the necessary inclusion of child participation in shaping programmes and policies and in helping to prevent or report violence. The question is: are these institutions keeping up with the pace of change? Are today’s models adapting to the constant evolution of child participation? This analysis of 10 approaches supports child rights practitioners in their efforts to promote effective child participation. Its ultimate goal is to unleash the positive power of millions of children who want to safeguard their right to a world free from violence.